JEM 2020
DOI: 10.17576/jem-2020-5402-07
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banking and Income Inequality: The Role of Corporate Social Responsibility

Abstract: The objective of this study is to analyse whether engaging more actively in corporate social responsibility (CSR) enhances the effectiveness of Islamic banks in narrowing income inequality in the selected Organization of Islamic Cooperation (OIC) countries. Both fixed-effect and random-effect models representing static model as well as generalized method of moments approach of dynamic model are employed to estimate the sample of 24 OIC countries for the period from 2006 to 2013. The results suggest that Islami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In regions within the Lower cluster, financing inequality can actually contribute to reducing the inequality of job opportunities. Our findings significantly update the conclusions made in Mohamad et al [11], Yuliani & Rohman [12], and Biancone et al [13], which previously suggested that Sharia financing has a positive impact on reducing income inequality in both high and low inclusion areas. As a consequence, it may be necessary to reevaluate these findings using a clustering approach, as we did in this study, to test the consistency of the results, given that the sample has traditionally been considered homogeneous.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In regions within the Lower cluster, financing inequality can actually contribute to reducing the inequality of job opportunities. Our findings significantly update the conclusions made in Mohamad et al [11], Yuliani & Rohman [12], and Biancone et al [13], which previously suggested that Sharia financing has a positive impact on reducing income inequality in both high and low inclusion areas. As a consequence, it may be necessary to reevaluate these findings using a clustering approach, as we did in this study, to test the consistency of the results, given that the sample has traditionally been considered homogeneous.…”
Section: Resultssupporting
confidence: 91%
“…Studies encompassing 24 member countries of the Organization of Islamic Cooperation (OIC) from 2006 to 2013 have shown that Islamic banks positively contribute to promoting equality [11]. Subsequent research further affirms the effectiveness of Islamic financing in mitigating inequality in both low-and high-income countries [12].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our research raises another important topic and that is social inequality. The work [12] shows the impact of Islamic accounting on the solvability of this problem. However, the work does not directly compare social responsibility of companies in the Western practice with that of Islamic banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The establishment of Islamic banking was a much awaited solution for Muslims seeking to accord their financial realm with their faith. High expectations were naturally placed directly on the shoulders of Islamic Banks (IBs) to not only serve the financial needs of the Muslim believers but also to manifest broader social justice principles (Dusuki, 2005;Iqbal and Mirakhor, 2012;Zaman, 2008;Hassan and Kayed, 2009;Ashraf et al, 2014;Mohamad et al, 2020;Sabiu and Abduh, 2021). The products offered by IBs have been subsequently demanded to satisfy each element of the society (Ayyub et al, 2019).…”
Section: Introductionmentioning
confidence: 99%